Speaking of grief and the grief of speaking: martyrs’ speech and the perils of translation - Kotrosits, Maia ca. 20./21. Jh. (Culture and religion, 2016)
In Derrida’s Monolinguism of the Other, a theory about the universal and constitutive alienation of the speaking subject from language finds its exemplary grounding in Derrida’s own experience as an Algerian Jew, one whose relationship to the French language is both totalizing and exiled (‘I have only one language, it is not mine.’). He equates speaking not only with contingent citizenship and a divestment of what one never really had in the first place, but also with the extreme experiences of torture, threat and physical violence. He indeed uses the words ‘passion’ and ‘martyr’ to describe his experience. In this paper, I will read Derrida ‘backwards,’ and against the universalizing move Derrida and those following him make in order to suggest a way of reading some scenes of violent death as scenes about diasporic cultural divestment. I’ll specifically attend to martyrs’ speech, and do so reading them as archives of the perils and inescapable expenses of entering dominant cultural ‘languages.’